Autophagy in the Regulation of Tissue Differentiation and Homeostasis - Perrotta, Cristiana; Cattaneo, Maria Grazia; Molteni, Raffaella; De Palma, Clara (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is a constitutive pathway that allows the lysosomal degradation of damaged components. This conserved process is essential for metabolic plasticity and tissue homeostasis and is crucial for mammalian post-mitotic cells. Autophagy also controls stem cell fate and defective autophagy is involved in many pathophysiological processes. In this review, we focus on established and recent breakthroughs aimed at elucidating the impact of autophagy in differentiation and homeostasis maintenance of endothelium, muscle, immune system, and brain providing a suitable framework of the emerging results and highlighting the pivotal role of autophagic response in tissue functions, stem cell dynamics and differentiation rates.